Perioperative Dexmedetomidine Improves Outcomes of Kidney Transplant - Chen, Jun (Clin Transl Sci, 2020)
Graft function is crucial for successful kidney transplantation. Many factors may affect graft function or cause delayed graft function (DGF), which decreases the prognosis for graft survival. This study was designed to evaluate whether the perioperative use of dexmedetomidine (Dex) could improve the incidence of function of graft kidney and complications after kidney transplantation. A total of 780 patients underwent kidney transplantations, 315 received intravenous Dex infusion during surgery, and 465 did not. Data were adjusted with propensity scores and multivariate logistic regression was used. The primary outcomes are major adverse complications, including DGF and acute rejection in the early post‐transplantation phase. The secondary outcomes included length of hospital stay (LOS), infection, overall complication, graft functional status, post‐transplantation serum creatinine values, and estimated glomerular filtration rate (eGFR). Dex use significantly decreased DGF (19.37% vs. 23.66%; adjusted odds ratio, 0.744; 95% confidence interval, 0.564–0.981; P = 0.036), risk of infection, risk of acute rejection in the early post‐transplantation phase, the risk of overall complications, and LOS. However, there were no statistical differences in 90‐day graft functional status or 7‐day, 30‐day, and 90‐day eGFR. Perioperative Dex use reduced incidence of DGF, risk of infection, risk of acute rejection, overall complications, and LOS in patients who underwent kidney transplantation.